The land of Israel in Bible, history, and theology : studies in honour of Ed Noort - Noort, Edward.; Ruiten, J. van; Vos, Jacobus Cornelis de, 1966- (Vetus Testamentum, Supplements, 2009)
This book deals with many aspects of the land of Israel. In the first part, the emphasis is on descriptions of the land in Joshua and other books of the Hebrew anf Greek Bible. In the second part, the focus shifts to the land in history and theology: reception-history of biblical texts dealing with the land, archaeology of Palestine, and theological-hermeneutical implications of taking the land traditions of the Bible seriously. The result is a rich collection of articles on one of the main themes of the Old Testament; a theme that has a fascinating, although not always unproblematic reception history.